Introduction to mass spectrometry 2 - Ruotolo, Brandon T. (Henry Stewart Talks, 2026)
Mass analyzer, Ion detectors, Tandem Mass Spectrometry (MS/MS), Key MS applications: proteomics and imaging, Native MS, Ion Mobility (IM)-MS, Chemical modifications strategies